ANALYSIS OF DAMAGED TURBINE BLADES OF THE ENGINE MPM 20 - Jozef Čerňan; Marián Hocko; Miroslava Cúttová; Karol Semrád (Acta Metallurgica Slovaca, 2016)
The objects of the investigation are damaged gas turbine blades of the MPM – 20 jet engine as a result of exceeding the temperature of the hot gases at the entrance of the gas turbine. On the damaged turbine blade metallographic-microscopic analysis was performed to identify aspects and consequences that accompanied the fracture. The research results showed phase changes in the structure as well as a significant oxidation along the grain boundaries, where cracks, leading to the destruction of the tip, were initiated. Toward the damage of the blades significantly contributed also the fact that higher temperatures cause higher thermal expansion and thus there was a clash of blades with an outer turbine casing. The subsequent mechanical deformation resulted in places of oxidized grains to cracking and a gradual detaching of the blade material in the form of partial fractures.